How does financial literacy impact on inclusive finance? - Morshadul Hasan; Thi Le; Ariful Hoque (Financial Innovation, 2021)
Inclusive finance is a core concept of finance that makes various financial products and services accessible and affordable to all individuals and businesses, especially those excluded from the formal financial system. One of the leading forces affecting people's ability to access financial services in rural areas is financial literacy. This study investigated the impacts of financial knowledge on financial access through banking, microfinance, and fintech access using the Bangladesh rural population data. We employed three econometrics models: logistic regression, probit regression, and complementary log-log regression to examine whether financial literacy significantly affects removing the barriers that prevent people from participating and using financial services to improve their lives. The empirical findings showed that knowledge regarding various financial services factors had significant impacts on getting financial access. Some variables such as profession, income level, knowledge regarding depositing and withdrawing money, and knowledge regarding interest rate highly affected the overall access to finance. The study's results provide valuable recommendations for the policymaker to improve financial inclusion in the developing country context. A comprehensive and long-term education program should be delivered broadly to the rural population to make a big stride in financial inclusion, a key driver of poverty reduction and prosperity boosting.
Keywords: D1; D9; G2; G4; G5; O2; R1; 650; Bangladesh; Bank; Financial inclusion; Financial knowledge; Financial literacy; FinTech; Inclusive finance; Knowledge economy; Microfinance